2020
DOI: 10.1002/ajmg.a.61611
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variants in EP300 and ANKRD11 in patients with phenotypes overlapping Cornelia de Lange syndrome

Abstract: Cornelia de Lange syndrome (CdLS), Rubinstein-Taybi syndrome (RSTS), and KBG syndrome are three distinct developmental human disorders. Variants in seven genes belonging to the cohesin pathway, NIPBL, SMC1A, SMC3, HDAC8, RAD21, ANKRD11, and BRD4, were identified in about 80% of patients with CdLS, suggesting that additional causative genes remain to be discovered. Two genes, CREBBP and EP300, have been associated with RSTS, whereas KBG results from variants in ANKRD11. By exome sequencing, a genetic cause was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Woods et al and Cucco et al have identified EP300 mutation in two patients with an initial diagnosis of Cornelia de Lange syndrome (CdLS, OMIM #122470, #300590, #610759, #614701, #300882, #608749) [ 162 , 163 ]. To date, six genes were implicated in the CdLS ( NIPBL , SMC1A , SMC3 , RAD21 , HDAC8 , and BRD4 ) and all of them encode proteins linked to the Cohesin complex [ 164 , 165 ] involved in chromatin organization and transcriptional regulation.…”
Section: Epigenetic Regulation and Cognitive Function In Rstsmentioning
confidence: 99%
“…Woods et al and Cucco et al have identified EP300 mutation in two patients with an initial diagnosis of Cornelia de Lange syndrome (CdLS, OMIM #122470, #300590, #610759, #614701, #300882, #608749) [ 162 , 163 ]. To date, six genes were implicated in the CdLS ( NIPBL , SMC1A , SMC3 , RAD21 , HDAC8 , and BRD4 ) and all of them encode proteins linked to the Cohesin complex [ 164 , 165 ] involved in chromatin organization and transcriptional regulation.…”
Section: Epigenetic Regulation and Cognitive Function In Rstsmentioning
confidence: 99%
“…Mutations in other genes have also been reported (reviewed in (Kline et al, 2018), Table 1): mutations in SMC1A have been identified in an estimated 5% of individuals with CdLS, usually associated to a non-classical phenotype (Musio et al, 2006;Borck et al, 2007;Deardorff et al, 2007;Ansari et al, 2014;Huisman et al, 2017); a SMC3 variant has been found in an individual with atypical CdLS (Deardorff et al, 2007) and others have been associated to individuals with some overlapping phenotypical features but not fulfilling the diagnostic criteria of non-classic CdLS (Ansari et al, 2014;Gil-Rodriguez et al, 2015); RAD21 variants have been found in a small percentage of non-classic CdLS cases ((Deardorff et al, 2012b) and reviewed in (Cheng et al, 2020)); HDAC8 variants have been also reported, with a typically heterogeneous non-classic phenotype, but also with some classic CdLS cases (Deardorff et al, 2012a;Harakalova et al, 2012;Ansari et al, 2014;Feng et al, 2014;Kaiser et al, 2014;Parenti et al, 2016;Helgeson et al, 2018;Jezela-Stanek et al, 2019); BRD4 mutations have been associated with few cases of non-classic CdLS (Olley et al, 2018;Alesi et al, 2019); and other gene variants have been identified, mainly by exome sequencing, associated with individuals with limited clinical CdLS features, like variants of EP300 (Woods et al, 2014;Cucco et al, 2020), AFF4 (Izumi et al, 2015), KMT2A (Yuan et al, 2015;Parenti et al, 2017;Aoi et al, 2019), NAA10 (Saunier et al, 2016), TAF6 (Yuan et al, 2015), ANKRD11 (Ansari et al, 2014;Parenti et al, 2016;…”
Section: Nipblmentioning
confidence: 99%
“…However, the diagnosis may be hard to achieve in individuals with atypical presentations, either because of phenotypic overlap with clinically and molecularly related disorders such as Cornelia de Lange syndrome or Floating-Harbor syndrome (Cucco et al, 2020;Hood et al, 2016), or the subtle presentation of physical features in some cases. The phenotypic spectrum of RSTS has been elucidated through multiple case reports and large cohort studies.…”
Section: Introductionmentioning
confidence: 99%